Sustainability reports and their impact on firm value: Evidence from Saudi Arabia - Younis, Nagat Mohamed Marie (International Journal of Management and Sustainability, 2023)
This study aimed to clarify the significance of sustainability reports and test the impact of the disclosure of sustainability reports on firm value. To achieve this end, the researcher conducted an applied study of the firms listed on the Saudi stock market during the period from 2017 to 2021. A sample of (60) firms was selected with a total number of 300 data points. Firm value was measured using four different measures: Tobin’s Q, market value per share, price/book value ratio per share, and security return. An indicator was created to measure the level of disclosure of sustainability reports and another to measure the quality of disclosure of sustainability reports. To measure the study’s variables, the content analysis method was used. Based on the results of the regression analysis, the study concluded that an intrinsic correlation exists between the level of disclosure of sustainability reports and the firm value, as well as a correlation between the quality of disclosure of sustainability reports and the firm value. The study recommends the following: First, an accounting standard for the disclosure of sustainability reports should be issued. Secondly, sustainable development criteria should be included in the academic criteria at Saudi universities. Thirdly, meetings with accountants and members of the Saudi capital market and firms should be held to find solutions to the challenges facing firms when preparing sustainability reports. Finally, further scientific research should be conducted in this field.